2022
DOI: 10.3390/polym14040838
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Additives and Environment on Biodegradation of PHBV Biocomposites

Abstract: The biodegradation of polyhydroxybutyrate-co-hydroxyvalerate (PHBV) ternary biocomposites containing nature-based plasticizer acetyl tributyl citrate (ATBC), heterogeneous nucleation agents—calcium carbonate (CaCO3) and spray-dried lignin-coated cellulose nanocrystals (L-CNC)—in vermicomposting, freshwater biotope, and thermophilic composting have been studied. The degree of disintegration, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and the evaluation of surface images taken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, the presence of a plasticizer could create some restrictions for food packaging applications in terms of toxicity and/or rapid migration from the polymer matrix. [ 59 ]…”
Section: Methods To Accelerate the Degradation Of Biodegradable Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of a plasticizer could create some restrictions for food packaging applications in terms of toxicity and/or rapid migration from the polymer matrix. [ 59 ]…”
Section: Methods To Accelerate the Degradation Of Biodegradable Polymersmentioning
confidence: 99%
“…However, the presence of a plasticizer could create some restrictions for food packaging applications in terms of toxicity and/or rapid migration from the polymer matrix. [59] The incorporation of fillers (at the micro and nano scale) could potentially provide two main functions: first, a reinforcement of mechanical and/or barrier properties during the service life of the plastic; and second, an incentive for water diffusion, swelling, and breaking of the polymer bulk (Figure 6). [88] It has been shown that hydrolysis of PLA nanocomposites is affected by the type of composite or filler, degradation and dispersion of the composite, and the polymer structure.…”
Section: Incorporation Of Additives During Processingmentioning
confidence: 99%
“…The presence of other pollutants and additives may impact biodegradation by affecting the surface properties of polymers, as well as the soil texture, moisture content, pH, and biota (Maddela et al 2022;Sajjad et al 2022). Plastics themselves frequently contain various amounts and types of substances added to improve the resilience and practical performances of native polymer chains, which could significantly alter the biological degradative response (Allen and Edge 2020;Brdlik et al 2022;Hahladakis et al 2018;Hermabessiere et al 2022;Sridharan et al 2022). The shape of plastic debris could be a relevant factor as well (Lehmann et al 2021).…”
Section: Soil and Plastic Biodegradationmentioning
confidence: 99%
“…There are slower degradation rates for polylactic acid PLA and polybutylene succinate PBS, and also the rate is sluggish in the case of polyethylene terephthalate PET (Al Hosni et al 2019;Larrañaga and Lizundia 2019;Qi et al 2022). Polyester biodegradation could be improved by copolymerization, as is the case of polybutylene adipate terephthalate PBAT, insertion of natural polyols, adipate and succinate diols in polyurethanes, or by mixing with additives or other biodegradable polymers like modified celluloses and PLA in blends or composites (Brdlik et al 2022;Erdal and Hakkarainen 2022;Schöpfer et al 2022).…”
Section: Bioresourcescommentioning
confidence: 99%
“…The most promising materials are polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polyhydroxyalkanoate (PHA), polybutylene adipate terephthalate (PBAT), polyhydroxybutyrate-co-hydroxyvalerate (PHBV), and their compounds [ 12 , 13 , 14 , 15 ]. The biodegradation rate greatly depends on the ambient temperature and humidity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%